Fertility preservation in a patient with benign multicystic peritoneal mesothelioma. Issue 4 (26th May 2014) - Al‐Safi, Zain A.; Edil, Barish H.; Post, Miriam D.; Pearlman, Nathan W.; Alvero, Ruben
<x xml:space="preserve">Abstract</x> Benign multicystic peritoneal mesothelioma (BMPM) is a rare peritoneal tumor. Surgery is the only effective treatment for BMPM, and affected tissues occasionally must be sacrificed to achieve adequate debulking. A 25‐year‐old female was diagnosed with BMPM. She was counseled on fertility preservation and had oocyte cryopreservation prior to her debulking. Fertility preservation through embryo or oocyte cryopreservation is a valuable option for patients at risk of losing reproductive tissues during extensive surgery and chemotherapy. J. Surg. Oncol. 2014; 110:372–374. © 2014 Wiley Periodicals, Inc.